SEASONAL ACTIVITY OF "TIGER" STRIPES ON SATURN'S MOON ENCELADUS - Vidmachenko, A.P. (Annali d'Italia, 2023)
The significant inclination of the plane of the satellite’s equator to the plane of the orbit of the central planet allows us to record differences in the flow of solar energy to different latitudinal zones during their rotation around the Sun. The equator of Enceladus, like Saturn itself, is inclined to the plane of the planet’s orbit by almost 27°. With a significant eccentricity of the planet's orbit (0.06), Enceladus and Saturn pass the perihelion of the orbit at a distance of 9 AU in summer in the southern hemisphere, and aphelion – at a distance of more than 10 AU during the summer season in the northern hemisphere. This leads to the fact that the southern hemisphere of Saturn and Enceladus receive on average a quarter more energy from the Sun than the northern. Such conditions affect on the influx of sunlight to the latitudinal zones and changes in physical characteristics on the surface of the satellite and in the atmosphere of the planet. The images obtained by “Cassini” devices show that almost the entire polar region is covered with fresh ice, shows geyser emissions, the presence of “tiger” stripes up to 130 km long, up to 2 km thick and up to 0.5 km deep. It is through them that water is released into the surrounding space from the ocean below the surface of the satellite. Spectral data obtained by “Cassini” equipment also indicated an abnormally high flow of heat through these bands, which are the source of water geysers. Our analysis showed that in 2022, Enceladus is moving from the polar day in the northern hemisphere, and is approaching the equinox in 2024-2025, and later – to the summer season in satellite southern hemisphere. And this should cause a significant increase in geyser activity in the polar region. Therefore, it will be useful to observe the seasonal increase in geyser activity in the “tiger” stripes around the satellite’s south pole, and to dedicate to this fact a special program of observations using infrared equipment on Keck telescopes, Very Large Telescope and space telescopes.